Torsion of caecal appendices epiploicae: mimicking acute appendicitis - Roshini, A. P.; Samant, Dattaprasad; Noronha, F. P. (International Surgery Journal, 2020)
Acute appendicitis is a common cause for pain in the right iliac fossa, which requires urgent surgical intervention. However, at the time of surgery, if the appendix is normal, the surgeon has to search for other causes of acute abdominal pain including rare etiologies, such as torsion of appendices epiploicae and subsequently its gangrene. We report the case of a 45 years old female who presented with right lower abdominal pain, rebound tenderness and guarding in right iliac fosse, with regular menstrual cycles and no urinary complaints. Investigation revealed leucocytosis and ultra-sonography abdomen was suggestive of an inflamed appendix in the right iliac fossa with free fluid. Intra-operatively, we found a normal appendix with gangrene of the appendices epiploicae which had undergone torsion. She underwent excision off appendices epiploicae with appendicectomy with uneventful post-operative period. Histopathology of the appendices was suggestive of congestion. Preoperative diagnosis of this condition is rarely made.